ANALISIS PERANCANGAN KEBUTUHAN KOPI BEST SELLER UNTUK MEMENUHI PERMINTAAN DI CAFE KOPI TITIK DENGAN MENGGUNAKAN METODE PERAMALAN - Santika Sari; Dhiyya Jannati (Bina Teknika, 2021)
The Covid 19 pandemic has an impact on industry in Indonesia. One of the industries affected by Covid 19 is the coffee shop industry. The existence of the Covid 19 pandemic caused uncertainty in the sale of coffee products which caused the coffee shop to have difficulty determining raw materials for the next period. To overcome this problem, forecasting is needed to determine the raw material needs in the form of coffee beans. This study aims to predict the number of best-selling products in "Kopi Titik" coffee. Namely coffee milk, Americano and Capuccino so that the company can get an idea of the number of product sales in the coming period. In addition, companies can also place orders with suppliers so that the raw material needs to fulfill best seller products can be met. The method used in this research is quantitative forecasting, that is forecasting that uses past data to determine future needs. The results obtained from this study are the best seller coffee sales pattern at the Point Coffee Cafe, namely a trend pattern which then uses the double exponential smoothing method with one parameter (Des Brown) and two parameter (Des Holt) approaches; MAPE from the forecast results is 0.268285274% for milk coffee, 0.36874754% for americano and 0.389056107% for cappuccino. The forecast results for the next 5 months are 3498 cups with details of 1920 cups of milk coffee, 754 glasses of americano and 824 cups of cappuccino.